The risk of aspirin induced postoperative hemorrhage: a systematic review and meta-analysis. (3rd October 2022) - Ling, Xin; Lin, Rong; Chen, Yanhong; Nie, Chi; Sheng, Liping; Liu, Jun; Han, Chaoqun; Ding, Zhen
ABSTRACT: Background and Objective: Current guidelines recommend aspirin maintenance for high-risk endoscopic procedures. Some Asian physicians noticed increasing postoperative bleeding in patients taking aspirin. We aimed to explore whether risk of postoperative hemorrhage due to aspirin differs in the East and the West. Methods: PubMed, EMBASE and Cochrane library database were systematically reviewed. We only included trials that met our criteria. Results: There is significant association between aspirin and postoperative bleeding (P < 0.001), especially in Eastern population (data from Japan, Korea, Turkey and China, P < 0.001). Result from the West (data from America, Canada and Australia) had no statistical significance (P = 0.07). For Easterners, aspirin increased bleeding risk after endoscopic submucosal dissection (ESD) and endoscopic sphincterotomy (EST). For Westerners, aspirin increased bleeding risk post endoscopic mucosal resection (EMR). For patients undergoing ESD, those who continued to receive aspirin had higher bleeding risk than patients who interrupted it for more than 7 days (P = 0.005). Conclusion: Aspirin increases risk of postoperative hemorrhage. Easterners are more likely to suffer from bleeding after aspirin administration than Westerners. Stopping aspirin for more than 7 days may be advisable to control bleeding post ESD for patients with low risk of thrombosis.